An energy-saving assessment approach for hood retrofitting in multi-cylinder dryer sections. Issue 15 (17th November 2016) - Yin, Yongjun; Li, Jigeng; Liu, Huanbin; Chen, Xiaobin
ABSTRACT: This study presents an integrated approach to assess energy performance during hood retrofitting from a semi-closed hood to a closed hood. According to the principle of heat and mass transfer, a simulation program was established by a mathematical model and some necessary model parameters. It could be used to simulate the paper-drying process and calculate steam and power consumption during paper drying. The method was applied to a corrugated paper machine. After a fundamental field test and observation, the simulation program determined appropriate model parameters. Finally, we found a 13.2% steam consumption reduction and a 13.5% total energy consumption reduction.